In conversation with Leo S. Klejn. (2nd November 2015) - Leach, Stephen
Abstract: This interview discusses the comparison that Klejn draws between archaeology and forensic science. This is a comparison that has been made many times previously by many different archaeologists (and crime writers), but Klejn is unusual in that he explores the implications of their similarity. In his view it is archaeology rather than history that is most closely related to forensic science. The difference between archaeology and history is important because when this difference was ignored, in the Soviet Union, it was to the detriment of both disciplines. Hence Klejn's continued concern – that the difference between archaeology and history is still, to some extent, ignored. Other subjects discussed include Klejn's view of the role of theory in relation to practice, his criticisms of New Archaeology and postprocessual archaeology, typology, the underlying principles of archaeology, ethnogenesis and the history of archaeology. Of course, in an interview of this length not all of these subjects are covered in great depth but it is hoped that enough is said that the reader may appreciate something of the nature and originality of Klejn's views.